2019
DOI: 10.1016/j.arthro.2018.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Acetabular Paralabral Cysts…It's All About Location, Location, Location…

Abstract: With our increased understanding about the causes of young adult hip pain and femoroacetabular impingement, magnetic resonance imaging has become an important diagnostic tool for identifying labral pathology. However, arthroscopic evaluation is paramount to understanding whether a labral tear truly exists in these patients. Orthopaedic dogma suggests that acetabular paralabral cysts form due to an associated acetabular labral tear. Nevertheless, a cause and effect relationship has not yet been proven in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, with a large number of clinical observations, it has been found that the so-called "impact" signs are also present in a large number of people without any hip symptoms. In this regard, many scholars have questioned the concept to a certain extent, questioning whether it has over-defined this so-called "impact" [15]. Checking the relevant domestic and foreign literature since the concept was put forward, there is no clear diagnosis standard and treatment indication for the disease at present.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…However, with a large number of clinical observations, it has been found that the so-called "impact" signs are also present in a large number of people without any hip symptoms. In this regard, many scholars have questioned the concept to a certain extent, questioning whether it has over-defined this so-called "impact" [15]. Checking the relevant domestic and foreign literature since the concept was put forward, there is no clear diagnosis standard and treatment indication for the disease at present.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…Labral tears frequently develop because of untreated cam and/or pincer morphology 1 . Labral injury can lead to paralabral cyst formation due to synovial fluid extravasating into the extra-articular space 2,3 . The incidence of paralabral cyst in patients with labral tears may be as high as 70% 5 .…”
mentioning
confidence: 99%